1986
DOI: 10.1002/ajmg.1320240107
|View full text |Cite
|
Sign up to set email alerts
|

The Wiedemann‐Beckwith syndrome: Pedigree studies on five families with evidence for autosomal dominant inheritance with variable expressivity

Abstract: We describe 18 individuals from five unrelated families with various manifestations of the Wiedemann-Beckwith syndrome. Pedigree analysis was performed on the 5 families and on another 19 families in the literature, each of which included more than one affected person. The following findings were obtained: 1) the clinical manifestations among the affected individuals were highly variable--those obvious in infancy tended to become less distinct with increasing age; 2) the syndrome was transmitted directly and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 18 publications
1
55
0
Order By: Relevance
“…Statistical and regression analyses of growth curve Data were compiled from original reports or reviews of nonoverlapping cases of BWS (Filipi and McKusick 1970;Sotelo-Avila and Singer 1970;Thorburn et al 1970;Kosseff et al 1976;Greenwood et al 1977;Shapiro et al 1982;McManamny and Barnett 1985;Niikawa et al 1986;Pettenati et al 1986;Takayama et al 1986;Takato et al 1989;Weng et al 1995b;Martínez y Martínez 1996) and SGBS (Simpson et al 1975;Behmel et al 1984Behmel et al , 1988Golabi and Rosen 1984;Opitz 1984;Tsukahara et al 1984;Neri et al 1988;Opitz et al 1988;Kö nig et al 1991;Garganta and Bodurtha 1992;Gurrieri et al 1992;Hughes-Benzie et al 1992a, 1996Chen et al 1993;Yamashita et al 1995). The frequency of occurrence of each manifestation (number of patients exhibiting a clinical feature as a fraction of total examined) is only indicative because of incomplete records.…”
Section: Somatic Overgrowth and Placentomegalymentioning
confidence: 99%
“…Statistical and regression analyses of growth curve Data were compiled from original reports or reviews of nonoverlapping cases of BWS (Filipi and McKusick 1970;Sotelo-Avila and Singer 1970;Thorburn et al 1970;Kosseff et al 1976;Greenwood et al 1977;Shapiro et al 1982;McManamny and Barnett 1985;Niikawa et al 1986;Pettenati et al 1986;Takayama et al 1986;Takato et al 1989;Weng et al 1995b;Martínez y Martínez 1996) and SGBS (Simpson et al 1975;Behmel et al 1984Behmel et al , 1988Golabi and Rosen 1984;Opitz 1984;Tsukahara et al 1984;Neri et al 1988;Opitz et al 1988;Kö nig et al 1991;Garganta and Bodurtha 1992;Gurrieri et al 1992;Hughes-Benzie et al 1992a, 1996Chen et al 1993;Yamashita et al 1995). The frequency of occurrence of each manifestation (number of patients exhibiting a clinical feature as a fraction of total examined) is only indicative because of incomplete records.…”
Section: Somatic Overgrowth and Placentomegalymentioning
confidence: 99%
“…However, data for adult height are inconclusive because of lack of information due to the discontinuation of follow-up after the usual period of surveillance for the occurrence of tumors. Several studies have reported patients in small cohorts to have a final height in the normal range [8,9,10,11], whereas others have reported adult heights exceeding +2 SDS [12,13,14,15,16,17,18] (table 1). …”
Section: Introductionmentioning
confidence: 99%
“…As children with BWS have a high risk for intra abdominal malignancies, especially Wilms' tu mor, hepatoblastoma, and neuroblastoma, fre quent sonogiaphical controls are necessary [5], Thegenetical background of BWS appears to be a mutation located on 11 p 15.5 [6]. In most familial cases, autosomal dominant in heritance with incomplete penetrance and variable expressivity was suggested [3,7], Some patients had structural anomalies of 1 lp [8], partly due to parental balanced trans locations [9]. The first prenatal diagnosis of BWS by ultrasound was performed in 1980 [10].…”
Section: Introductionmentioning
confidence: 99%